Cystic fibrosis transmembrane conductance regulator chloride channel blockers: Pharmacological, biophysical and physiological relevance - Linsdell, Paul (Baishideng Publishing Group Co., Limited, 2014)
Dysfunction of the cystic fibrosis transmembrane conductance regulator (CFTR) chloride channel causes cystic fibrosis, while inappropriate activity of this channel occurs in secretory diarrhea and polycystic kidney disease. Drugs that interact directly with CFTR are therefore of interest in the treatment of a number of disease states. This review focuses on one class of small molecules that interacts directly with CFTR, namely inhibitors that act by directly blocking chloride movement through the open channel pore. In theory such compounds could be of use in the treatment of diarrhea and polycystic kidney disease, however in practice all known substances acting by this mechanism to inhibit CFTR function lack either the potency or specificity for in vivo use. Nevertheless, this theoretical pharmacological usefulness set the scene for the development of more potent, specific CFTR inhibitors. Biophysically, open channel blockers have proven most useful as experimental probes of the structure and function of the CFTR chloride channel pore. Most importantly, the use of these blockers has been fundamental in developing a functional model of the pore that includes a wide inner vestibule that uses positively charged amino acid side chains to attract both permeant and blocking anions from the cell cytoplasm. CFTR channels are also subject to this kind of blocking action by endogenous anions present in the cell cytoplasm, and recently this blocking effect has been suggested to play a role in the physiological control of CFTR channel function, in particular as a novel mechanism linking CFTR function dynamically to the composition of epithelial cell secretions. It has also been suggested that future drugs could target this same pathway as a way of pharmacologically increasing CFTR activity in cystic fibrosis. Studying open channel blockers and their mechanisms of action has resulted in significant advances in our understanding of CFTR as a pharmacological target in disease states, of CFTR channel structure and function, and of how CFTR activity is controlled by its local environment.